Kansas agricultural land turnover - Hinds, Alan (Kansas State University, 2023)
Agricultural land represents approximately 80% of assets on the farm balance sheet, while serving as the principal input in agricultural production. Access to land is critical for the success of farmers, especially those considered new and beginning. The overall market for agricultural land can be broken into two primary submarkets: the rental market and ownership market. As such, literature on the ownership market largely focuses on prices or estate planning, with little regard to transaction volumes or frequency and the determinants of a transaction. Transaction volumes and frequency have been studied in the financial and real estate literatures, largely motivated by efficiency and liquidity concerns. Farmland markets are unique in that they operate imperfectly with high transaction costs and relatively few open market transactions. Transactions off the open market include inheritance and private sales. Policies that decrease the amount of land that is transacted may lead to economic or efficiency losses in farmland markets. While this study is motivated by the first-order efficiency and equity implications of farmland turnover, nearly all of the previous real estate and corporate finance research that analyzed transactions volume was largely motivated by market liquidity. This study thus begins by examining this literature and clarifying how turnover relates to broader concepts of market efficiency, before an empirical examination of farmland turnover. Utilizing individual Kansas agricultural land transactions since 1985 aggregated to the county level, the rate of turnover is calculated, determinants of turnover are identified, and sale-type differences surrounding arms-length transactions and use of land are explored. We find that farm income indicators, indicators of the general US economy, and demographic factors all generally predict farmland turnover. Current farm economy indicators have a weak and inconsistent relationship with turnover, but several lagged indicators of high farm income predict either higher or lower turnover. A strong general or nonfarm economy is related to higher turnover. As our model estimates net effects, we cannot identify whether turnover is driven by exits driven by financial stress or planned retirement, for which farm income and general economy indicators would have different effects. However, we do establish that these factors are relevant to turnover and find evidence that the expectations or financial conditions that drive turnover are formed over several years. Demographic factors are also relevant, with higher average age related to higher turnover but more operators over 65 related to lower turnover. This jointly provides evidence that relatively older operators demand land, but that retirement-aged operators have incentives to hold land for inheritance. At a foundational level in the literature, this research provides new insights into an understudied area of the U.S. agricultural land market. Understanding the frequency at which agricultural land transacts is critical to developing and amending many policies. The implications of policies aimed at reducing or eliminating stepped-up basis, increasing land access for new and beginning farmers, and many others, can be informed by an understanding of the factors that affect this key component of the market. Further research motivated from this work may expand to causal identification of, analysis of policy changes, or inclusion of additional geographies.
Keywords: Farmland; Agricultural land; Turnover; Liquidity; Transaction frequency